Membangun Disiplin Rohani Siswa pada Generasi Z Melalui Jurnal Membaca Alkitab [Building Students' Spiritual Discipline of Generation Z through Bible Reading Journalling] - Vrijilio Aditia Apaut; Suparman Suparman (Universitas Pelita Harapan, 2021)
Reading the Bible as spiritual discipline is a very important part of every Christians’ life. Through Bible reading one might build closer relationships with the Triune God, growing in the knowledge of God, aware of the sins, and build good Christian character. But Z generation are no longer concerned with this spiritual discipline as it is influenced by the negative aspects of advanced technological developments. The purpose of this paper is to reveal the importance of the spiritual discipline of Bible reading to students. The Bible reading Journal is one of the guidelines that directs students to read the Bible every day according to the part that has been planned. The process of spiritual discipline to read the Bible is the work of the Holy Spirit to every believer in helping them to have a relationship with Triune God. The conclusion is that the Bible reading journal is a practical step in building the spiritual discipline of reading the Bible that can involve the cooperation between parents and teachers.